Competencia desleal en productos importados del sector alimenticio: una mirada hacia los consumidores. (2020)
Colombia in its different departments has a diverse vision regarding the import of food and its production, however, the way these products are introduced to the market is done unfairly; The objective is to explore unfair competition, based on current regulations, taking as a reference the experiences of Palmira consumers in relation to imported food products. Using an exploratory and descriptive method to establish whether consumers of imported and national food have ever witnessed a case of unfair competition, clearly to know and rule an analysis applying a quantitative and qualitative approach, the result was that 77,5% of the population of Palmira has knowledge on the subject and it is highlighted that of the total of respondents, 54.5% have concentrated on acts of confusion and 45.5% have had experience with acts of deception. It also ends with recommendations for individuals to consider actions in case of filing an act of unfair competition.